Comparative Performance of Creatinine-Based GFR Estimation Equations in Exceptional Longevity: The Rugao Longevity and Ageing Study - Wang M (Dove Medical Press, 2020)
Mengjing Wang,1,2,* Xuehui Sun,3,* Li Ni,1 Minmin Zhang,1 Jiaying Zhang,4 Guoxin Ye,1 Li Jin,2,3 Xiaofeng Wang,2,3 Jing Chen1,2 1Nephrology, Huashan Hospital, Fudan University, Shanghai, People’s Republic of China; 2National Clinical Research Center for Aging and Medicine, Huashan Hospital, Fudan University, Shanghai, People’s Republic of China; 3State Key Laboratory of Genetic Engineering and Ministry of Education Key Laboratory of Contemporary Anthropology, School of Life Sciences, Fudan University, Shanghai, People’s Republic of China; 4Nutrition, Huashan Hospital, Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Chen; Xiaofeng Wang Email chenjing1998@fudan.edu.cn; xiaofengwang71@163.comPurpose: Reduced kidney function has been associated with an increased risk for adverse outcomes. Accurate assessment of glomerular filtration rate (GFR) is key to diagnosis and management of kidney disfunction. Debate exists on the best GFR estimation equation for elderly people. This study aimed to compare the predictive validity and discriminative ability of four GFR equations in relation to 2-year and 6-year mortality in exceptional longevity (EL) (those over 95 years old with intact health) individuals and is an ideal model to address factors relating to life span and age-related diseases.Patients and Methods: This study used 6 years’ data of 278 EL from the Rugao longevity cohort. Baseline GFR was estimated using four equations: Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation, Modification of Diet in Renal Disease Study (MDRD) equation, Berlin Initiative Study-1 (BIS) equation, and modified MDRD equation. Predictive validity was tested using Cox proportional hazards analysis. Overall improvement in reclassification based on estimated GFR (eGFR) was assessed applying net reclassification improvement (NRI).Results: Mean age of participants was 97± 2 years with median follow-up of 2.6 years. Median (IQR) eGFR by CKD-EPI, MDRD, BIS, and modified MDRD equations were 73.9 (62.2– 77.6), 82.3 (67.4– 98.6), 56.4 (47.9– 63.9), and 101.5 (83.1– 121.6) mL/min per 1.73 m2, respectively. Higher eGFREPI was associated with lower mortality after multivariate adjustment (for continuous eGFREPI, HRtwo-year 1.018, 95% CI 1.002– 1.033, P=0.023; HRsix-year 1.013, 95% CI 1.002– 1.025, P=0.022), while eGFR from other equations did not show any associations with mortality. NRI for two-year mortality was 0.14 and approximately significant, which may favor the CKD-EPI when compared to BIS equation (P=0.052).Conclusion: The CKD-EPI equation showed more accurate estimation of kidney function in the elderly with respect to GFR distribution and predictability of mortality risk.Keywords: glomerular filtration rate, kidney function, equation, exceptional longevity, mortality